ANALYSIS OF GREEN ECONOMY VARIABLES ON INDONESIA'S NATIONAL INCOME IN 2018-2023 FROM AN ISLAMIC ECONOMIC PERSPECTIVE - M Rangga Wirdinata; Asriani Asriani; Yulistia Devi (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2026)
Sustainable economic development through the green economy is a crucial solution for Indonesia to balance economic growth with environmental conservation. This study aims to analyze the relationship of green economy variables which include carbon (CO2) emissions, green investment, and renewable energy to Indonesia's national income in the 2018–2023 period from an Islamic economic perspective. The research method used is a quantitative approach with multiple linear regression analysis techniques to objectively measure the relationships between variables through numerical data. Secondary data were obtained from the World Bank, the Central Statistics Agency, and the Ministry of Environment and Forestry. The results showed that simultaneously, the variables of carbon emissions, green investment, and renewable energy had an effect on national income at a significance level of 10%, with a determination coefficient value (R-squared) of 0.9541. However, partially, these three variables do not have a significant effect on Indonesia's national income at the standard level of 5%. This insignificance is suspected to be influenced by the limited number of observations (n=6) as well as the initial transition phase of the green economy in Indonesia. In conclusion, national economic management must remain based on the principles of maslahah, trust, and balance (tawāzun) to achieve long-term prosperity. The recommendation of this study is to strengthen the integration of Islamic social financial instruments such as Green Sukuk and ZISWAF to encourage sustainable renewable energy projects.